The Dynamics Of The Atmospheric Pollutants During The Covid-19 Pandemic 2020 And Their Relationship With Meteorological Conditions In Moscow - N. Ye. Chubarova; Ye. Ye. Androsova; Ye. A. Lezina (GEOGRAPHY, ENVIRONMENT, SUSTAINABILITY, 2021)
The relationship between the dynamics of the atmospheric pollutants and meteorological conditions has been analyzed during the COVID-19 pandemic in Moscow in spring, 2020. The decrease in traffic emissions during the lockdown periods from March 30th until June 8th played an important role in the decrease (up to 70%) of many gaseous species and aerosol PM10 concentrations and in the increase of surface ozone (up to 18%). The analysis of the pollutant concentrations during the lockdown showed much smoother diurnal cycle for most of the species due to the reduced intensity of traffic, especially during rush hours, compared with that before and after the lockdown. The specific meteorological conditions with low temperatures during the lockdown periods as well as the observed smoke air advection have made a considerable contribution to the air quality. After removing the cases with smoke air advection the decrease in concentration of many pollutants was observed, especially in NOx and PM10. The analysis of Pearson partial correlation coefficients with fixed temperature factor has revealed a statistically significant negative correlation between the Yandex self-isolation indices (SII), which can be used as a proxy of traffic intensity, and daily concentrations of all pollutants, except surface ozone, which has a statistically significant positive correlation with SII caused by specific photochemical reactions. In situations with SII>2.5 more favorable conditions for surface ozone generation were observed due to smaller NOx and the higher O3 /NOx ratios at the same ratio of VOC/NOx. In addition, this may also happen, since during the Arctic air advection, which was often observed during the lockdown period, the growth of ozone could be observed due to the downward flux of the ozone-rich air from the higher layers of the atmosphere.